Biosynthesis and antibacterial potential of tectona grandis mediated magnesium oxide nanorods. - Maishera, HA; Kuta, FA; Tijani, JO; Adabara, NU; Adedeji, AS; Bala, JD (Journal of Bio-Science, 2019)
The high rate of enteric bacterial infection and the increasing drug resistance by pathogenic bacteria have made the search for new antimicrobials inevitable. The aim of the study was to investigate the antibacterial potentials of Tectona grandis magnesium oxide (MgO) nanorods on clinical isolates of Escherichia coli Acj 213, Salmonella Typhi strain T8 and Pseudomonas aeruginosa strain DMI. Magnesium chloride solution (50 ml, 1M) was bio reduced to magnesium oxide nanorods using Tectona grandis leaves extract (10 ml). The biosynthesized nanoparticles were characterized using UV-visible spectroscopy (UV-vis), dynamic light scattering (DLS), high resolution transmission electron microscopy (HRTEM), surface area electron diffraction analysis (SAED) and X-ray diffraction techniques (XRD). Similarly, antibacterial effects of the MgO nanorods were determined using agar well diffusion technique. The biogenic MgO nanorods colloidal solution was fluffy brown in colour with UV-Vis absorbance peak occurring at 364 nm. The DLS analysis revealed monodispersed MgO nanorods with 90 nm hydrodynamic diameter. Furthermore, the XRD analysis showed that the crystalline nature had average size of 30 nm. HRTEM/SAED result revealed a rod shaped polycrystalline MgO nanorods with 29 nm average size. The results of the antibacterial test showed that MgO nanorods had the highest antimicrobial activity (21.75 ± 1.79 mm, 22.75 ± 1.70 mm and 19.75 ± 1.10 mm) at 500 mg/ml against E. coli Acj 213, S. Typhi strain T8 and P. aeruginosa strain DMI, respectively. The minimum inhibitory concentration for P. aeruginosa strain DMI, S. Typhi strain T8 and E. coli Acj 213 were 125 mg/ml, 62.5 mg/ml and 125 mg/ml, respectively. However, the minimum bacteriocidal concentration was 250 mg/ml, 125 mg/ml and 250 mg/ml, respectively. The results of this study indicate that the synthesized MgO nanorods could be a potential antibacterial agent with broad spectrum activities. J. bio-sci. 27: 109-120, 2019